Fatal outbreak of an emerging clone of extensively drug-resistant Acinetobacter baumannii with enhanced virulence - Jones, Crystal L; Clancy, Megan; Honnold, Cary; Singh, Shweta; Snesrud, Erik; Onmus-Leone, Fatma; McGann, Patrick; Ong, Ana C; Kwak, Yoon; Waterman, Paige; Zurawski, Daniel V; Clifford, Robert J; et al. (Clinical infectious diseases, 2015)
BACKGROUND: Severe Acinetobacter baumannii infections in immunocompetent patients are uncommon, and the virulence mechanisms of this organism are not fully understood. METHODS: Following an outbreak of fatal A. baumannii infections in a cohort of relatively immunocompetent patients (low comorbidity and illness severity scores), isolates were investigated with comparative genomics and in animal models. RESULTS: Two unrelated A. baumannii clades were associated with the outbreak. The clone associated with the majority of patient deaths, clade B, is evolutionarily distinct from the 3 international clonal complexes, belongs to multilocus sequence type (MLST) 10, and is most closely related to strains isolated from the Czech Republic, California, and Germany in 1994, 1997, and 2003, respectively. In 2 different murine models, clade B isolates were more virulent than comparator strains, including the highly virulent reference strain AB5075. The most virulent clade B derivative, MRSN 16897, was isolated from the patient with the lowest combined comorbidity/illness severity score. Clade B isolates possess a unique combination of putative virulence genes involved in iron metabolism, protein secretion, and glycosylation, which was leveraged to develop a rapid and specific clinical assay to detect this clade that cannot be distinguished by MLST. CONCLUSIONS: Clade B warrants continued surveillance and investigation.
Keywords: centra terciární péče; California; Spojené státy americké; extensively drug resistant; Humans; Kalifornie; Phylogeny; mnohočetná bakteriální léková rezistence; lidé středního věku; Acinetobacter Infections; Multilocus Sequence Typing; Disease Outbreaks; Female; dospělí; genomika; Virulence; infekce bakteriemi rodu Acinetobacter; outbreak; lidé; zvířata; myši; virulence; United States; Germany; Drug Resistance, Multiple, Bacterial; Mice; Německo; Adult; Acinetobacter baumannii; Immunocompetence; ženské pohlaví; Male; Middle Aged; fylogeneze; multilokusová sekvenční typizace; Czech Republic; Aged, 80 and over; Tertiary Care Centers; senioři nad 80 let; Animals; Česká republika; mužské pohlaví; Genomics; Disease Models, Animal; epidemický výskyt choroby; imunokompetence; modely nemocí na zvířatech